Design and Implementation of Active Control Method for Minimizing Circulating Current in MMC-VSC System - A. Aslam; M. Raza (IEEE Access, 2025)
Modular Multilevel Converters (MMCs) have emerged as a key technology for large-scale renewable energy integration due to their scalability, fault tolerance, and superior output quality. However, internal circulating currents remain a major barrier to efficiency and long-term reliability. It causes power losses, increased thermal stress, and excessive capacitor voltage fluctuations. Existing passive and active methods often lack clear design guidelines or fail to achieve robust suppression under varying operating conditions. This paper introduces a comprehensive hybrid strategy that addresses these gaps through two key innovations. Firstly, an analytical expression for arm inductor sizing is derived using instantaneous power theory and the harmonic addition theorem. It offers an explicit passive design method rather than relying on heuristic selection. This analytical formulation ensures optimal passive suppression within practical inductor size constraints. Then an advanced active suppression scheme is developed. Unlike conventional approaches, the circulating current is regulated using a vector control strategy formulated in the dq reference frame. It enables precise control of the dominant second-order harmonic. The PI controller is tuned through a direct pole placement method. A high-pass filter is integrated upstream of the controller to eliminate the DC offset. The simulation studies demonstrates that the proposed methods outperforms traditional direct modulation by significantly reducing circulating current amplitude, lowering power losses and improving thermal performance. The results confirm that the passive and active control framework delivers a robust, scalable, and practically implementable solution for next-generation MMC-based renewable energy systems.